The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/rem.21526
|View full text |Cite
|
Sign up to set email alerts
|

Chemical oxidation using stabilized hydrogen peroxide in high temperature, saline groundwater impacted with hydrocarbons and MTBE

Abstract: In situ chemical oxidation (ISCO) of petroleum hydrocarbons (PHCs) within groundwater is considered a proven approach to addressing PHC‐impacted groundwater in nonsaline environments. One of the most common oxidants used for oxidation of PHCs in groundwater is hydrogen peroxide (H2O2). Due to its highly reactive nature, H2O2 is often stabilized to aid in increasing its reactivity lifespan. Limited research and application of ISCO has been completed in warm, saline groundwater environments. Furthermore, even fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 27 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Previous laboratory experiments by Kashir et al () on groundwater collected from the site indicated that no significant δ 13 C shift occurred for benzene during oxidation by sodium persulfate until benzene concentrations declined by at least 50%. During the pilot test, a shift in the δ 13 C occurred before a decrease in the benzene concentration suggesting a more complex relationship between the benzene sorbed to the soil and groundwater.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous laboratory experiments by Kashir et al () on groundwater collected from the site indicated that no significant δ 13 C shift occurred for benzene during oxidation by sodium persulfate until benzene concentrations declined by at least 50%. During the pilot test, a shift in the δ 13 C occurred before a decrease in the benzene concentration suggesting a more complex relationship between the benzene sorbed to the soil and groundwater.…”
Section: Resultsmentioning
confidence: 86%
“…Previous laboratory studies using site‐specific groundwater showed greater hydrogen enrichment relative to δ 13 C during biodegradation of benzene (Kashir et al, ). During the ISCO phase of the pilot test, δ 13 C and δ 2 H in benzene data indicated similar magnitudes of enrichment.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Laboratory microcosm testing using site media and a variety of stabilization reagents including silica dioxide, phytate, and citrate indicated that greater than 95% of the target hydrocarbons were removed within 7 days of treatment (Kashir & McGregor, ). Microcosms with citrate‐stabilized H 2 O 2 demonstrated a significantly faster and greater concentration decrease with most hydrocarbon concentrations reaching <5 micrograms per liter (μg/L).…”
Section: Introductionmentioning
confidence: 99%
“…MTBE declined from >400 milligrams per liter (mg/L) to <100 mg/L in all microcosms, again with the best removal (>90%) being measured in the citrate‐stabilized microcosms. Unfortunately, H 2 O 2 oxidation in the microcosms also resulted in production of up to 40 mg/L TBA or approximately 10% of the MTBE oxidized (Kashir & McGregor, ).…”
Section: Introductionmentioning
confidence: 99%